Effect of Diabetes and Hypertension on Right Carotid Artery Intima Media Thickness and Variable Spectral Waveform Indices And Parameters in Relation To Age for Iraqi Patients (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Arterial stiffness is related with atherosclerosis and cardiovascular disease events. Patientswith atherosclerotic disease show to have larger diameters, reduced arterial compliance and lower flowvelocities.Aim of study : To compare between patients of two age groups with concomitant diseases diabetes andhypertension in regard to intima media thickness and blood flow characteristics in order to estimate theblood perfusion to the brain via the common and internal carotid arteries.Subject and Methods : 40 patients with (diabetic and hypertension) diseases were enrolled , they wereclassified according to age. Color Doppler and B mode ultrasound was used to determine lumen Diameter(D), Intima – media thickness (IMT), end diastolic velocity (EDV), peak systolic velocity (PSV), ResistiveIndex (RI), Pulsatility Index (PI), and the flow rate indices were calibrated and calculated .Results:- Results show that the change in the lumen diameter between the old patients group and the youngergroup were (2.02%) with insignificant (p value >0.05), and the difference in the in intima-media (IMT)thickness between the two age groups (35- 55) and (56-75) are (33.8%) with significant (p value <0.05).The change difference in peak systolic velocity was (-13.29% ) with insignificant (p value >0.05), while thedifference in the (EDV) between both age groups was (-38.02%), with significant p value <0.05. Pressuregradient and flow rate have given insignificant difference between both age groups.Conclusion: The intima media is significantly thicker for the old age group than in the younger group. Theincreased thickness of intima media did not influence the lumen diameter significantly. A clear change inPSV, EDV, RI, and PI was observed which have influenced blood perfusion to the brain.